MORAL SEKS DALAM CERITA PEWAYANGAN - Rahno Triyogo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2010)
Sex (intercourse) represents  a relation of two personalities that is between a husband and a wife involving  physic, feeling, emotion, and the soul based on love and mutual respect.  Sex that is executed by unmarried couple is supposed to be  adultery sin and immoral in some  religions as well as cultures. Each culture against the adultery so that people who does the adultery will  get a heavy moral sanction. The moral sanction means the fall of  the man’s dignity as a cultured human being. Key words:  sex (intercourse), moral, dignity